Answer:
Explanation:
Slope-intercept form: y = mx + b
Slope formula:
Given points: (2, 1), (-4, -2)
(2, 1) = (x1, y1)
(-4, -2) = (x2, y2)
To write the equation in slope-intercept form we need to find the slope(m) and the y-intercept(b) of the equation.
First, let's find the slope. To do this, input the given points into the formula used to find slope:
Simplify:
-2 - 1 = -3
-4 - 2 = -6
The slope is
. We can input the slope and one of the given points (in this example I'll use point (2, 1)) into the equation to find b:
1 = 1 + b
0 = b
The y-intercept is 0. Now that we know the slope and the y-intercept, we can write the equation: